Measuring Design and its Role in Innovation - Galindo-Rueda, Fernando (OECD Science, Technology and Industry Working Papers, 2015)
This working paper sums up the main findings of an OECD project aiming to provide an evidence basis for focusing efforts to improve the measurement of technological and non-technological forms of business innovation, with particular focus on the role of design. It reviews a broad range of novel design-related measures, indicating their advantages and limitations in terms of policy relevance and insights. The analysis of design provides a valuable test-case for assessing the robustness of the overall framework for measuring innovation as proposed in the OECD/Eurostat Oslo Manual. It identifies a number of areas for potential development in a future revision, focused on the role of users and the implementation of the definition of innovation and innovation activities. It also identifies a range of design concepts based on an informal consultation with the design expert community. The paper also illustrates a number of findings arising from the first-time use of a set of experimental and optional questions on design implementing a "ladder-type" model of design which describes levels of sophistication and integration of the design function within the firm. Cognitive testing and analysis of the microdata from a large and representative sample of Danish firms shows a high degree of respondent acceptance of the experimental questions and supports their predictive validity vis-à-vis a number of hypotheses on the use of design and a series of innovation and economic outcomes potentially associated to it